Naval Arms Race Between Argentina, Chile and Brazil (1891-1923) [Las Carreras Armamentistas Navales Entre Argentina, Chile y Brasil (1891-1923)] - Garay-Vera, C (Universidad de los Andes, Bogota Colombia, 2012)
The overview of the issue of South American naval competition between the late nineteenth and early twentieth century has been hindered by a bilateral perspective. Based on a perception of the hard power, naval competition is not interpreted as an episode restricted to the case of Chile-Argentina or Argentina-Brazil, but as a regional political determination induced by the belief that naval competition would increase the chances for success in the international system. This search for prestige ended in the 1920s due to cultural reasons, Wilsonianism, the path of collective security being discredited after World War I, and the global pro-disarmament climate.
Keywords: Latin American history; peace; international security; arms race; arms control